Implications of Exercise-Induced Pulmonary Arterial Hypertension - Fowler, R.; Maiorana, Andrew; Jenkins, Susan; Gain, Kevin; O'Driscoll, G.; Gabbay, E. (Lippincott Williams & Wilkins, 2011)
Purpose: To characterize the hemodynamic and ventilatory responses to exercise in a group of patients with unexplained dyspnea, increased risk for pulmonary arterial hypertension (PAH), and an elevated mean pulmonary artery pressure (mPAP; >30 mm Hg) on exercise. Methods: A total of 37 symptomatic patients at risk of PAH and 20 healthy controls underwent a cardiopulmonary exercise test and were assessed for quality of life (QOL). Patients had a pulmonary artery catheter in situ during the exercise test. Results: Seventeen subjects had exercise-induced PAH (EIPAH), which we defined as mPAP ≤ 25 mm Hg at rest, and mPAP > 30 mm Hg and pulmonary artery wedge pressure <20 mm Hg on exercise. These subjects had reduced peak exercise cardiac output (72% ± 19% predicted). Further, compared with matched controls, subjects with EIPAH had reduced peak oxygen consumption (1.2 ± 0.4 vs 1.7 ± 0.5 L•min−1, P < 0.05), an elevated ventilatory equivalent for carbon dioxide (41.0 ± 7.3 vs 31.0 ± 2.9, P < 0.05) and reduced end-tidal carbon dioxide tension (32.6 ± 3.6 vs 39.4 ± 2.7 mm Hg, P < 0.05) at the anaerobic threshold. These exercise abnormalities were associated with impaired QOL (P < 0.05). Conclusions: Elevated pulmonary artery pressure on exercise can be associated with hemodynamic and ventilatory abnormalities typical of PAH, along with impaired exercise capacity and reduced QOL.